Diseño e implementación de un algoritmo de seguimiento de trayectorias para el minidron Parrot mambo utilizando – Simulink/Stateflow (2022)
This document presents the proposal for the design and implementation of a trajectory tracking algorithm that will be incorporated into the flight control system of the Parrot Mambo minidrone, with the aim of performing autonomous flights. The tracking algorithm will be developed in three phases: initially a sequence of images will be processed through three processes that are; binarization, segmentation, and pixel counting, then the algorithm will be designed through the design of the state machine for data acquisition and processing and finally the algorithm will be validated through Simulink/Stateflow considering four scenarios where it will be tested the performance. Likewise, in the development of this document, an effectiveness of 93.33% success was demonstrated in the different performance tests of the algorithm, and part of the efficiency is presented in the data collection, the pulses emitted by the different sensors that were generated from the image, the duration of each pulse is variable and can range from 9 s to end at 18 s, and the response time seen in the final movement of the drone lasts exactly the time that the pulses take